Group work: A learning barrier? - Grossi, Alberto (Improving University Science Teaching and Learning, 2023)
During Block 1 2010 I was involved for the first time in “Physical and Chemical Changes of Food Quality” in the Department of Food Science, Faculty of Life Sciences. Inspired by “Teaching for Quality Learning at University” (Biggs & Tang; 2007) and by stimulating discussions with pedagogical supervisors and colleagues, I started thinking about how I could design some learning activities that could make group work (GW) the centre of a stimulating and involving learning experience. In this project, I intended to discuss the use of GW as a teaching tool and to suggest that learning experiences will be more effective if planned in a structured way with teachers taking account of the relationships between group size, interaction type and the nature of the intended learning task.